E-learning Challenges during the Covid-19 Pandemic Experienced by Students - Siti Safura (Universitas Ahmad Dahlan, 2021)
The spread of the covid-19 pandemic has changed the teaching and learning process from conventional to e-learning classes. This e-learning class brings out the challenges for students, educators, parents, and institutions. This present study was aimed to see the e-learning challenges faced by students during the Covid-19 pandemic. The participants of this study were 40 students at the Islamic Faculty of Muhammadiyah Aceh University. The qualitative descriptive was applied to analyze 20 questionnaires that were distributed through a google form. The questionnaire was divided into four sessions of challenges that involve internet connectivity, facilities support, technology competence, and self-regulation. This study revealed that students faced problems with the internet, devices, and self-regulation, while technology competence did not show significant challenges.